INTEGRASI NILAI-NILAI ISLAM SISWA DALAM PEMBELAJARAN FIKIH DI MI TANWIRUL HIJA CANGKRENG SUMENEP - Rif’atul Fadilah; Muqawim; Jonata; Ahmad Saufi Al Hadisi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Education is a conscious effort made to provide a learning experience for students. This experience consists of cognitive, affective, and psychomotor aspects. This research is motivated by the state of education in elementary schools with learning that is less focused on integrating one science with one another. This research is a qualitative research with the type of case study. Sources of data are teachers and students in SD/MI who were selected by purposive sampling. The technique used is interview and observation technique with interview sheet instruments and field notes on the reality of the implementation of education in schools. The results of the study indicate that the integration of Islamic values ​​in Fiqh learning greatly affects student actions during learning. Students can provide good and easy thoughts, and can dissect material that is incorporated and interconnected with everyday life. Through this integrative learning, Islamic traits are also hidden in the students which are then instilled in a straightforward manner through mentality and behavior in everyday life.